Electrochemical Arylation of Electron‐Deficient Arenes through Reductive Activation. Issue 44 (17th September 2019) - Wang, Pan; Yang, Zhenlin; Wang, Ziwei; Xu, Chenyang; Huang, Lei; Wang, Shengchun; Zhang, Heng; Lei, Aiwen
Abstract: An electrochemical method has been developed to achieve arylation of electron‐deficient arenes through reductive activation. Various electron‐deficient arenes and aryldiazonium tetrafluoroborates are amenable to this transformation within the conditions of an undivided cell, providing the desired products in up to 92 % yield. Instead of preparing diazonium reagents, these reactions can begin from anilines, and they can be carried out in one pot. Electron paramagnetic resonance studies indicate that cathodic reduction of quinoxaline occurs using the transformation. Moreover, cyclic voltammetry indicates that both quinoxaline and aryl diazonium salt have relatively low reduction potentials, which suggests they can be activated through reduction during the reaction. Abstract : An electrochemical method was developed for arylation of electron‐deficient arenes through reductive activation. Various electron‐deficient arenes and aryldiazonium tetrafluoroborates were examined for the transformation within an undivided cell, furnishing the desired products with up to 92 % yield. Reduction of quinoxaline is a key step in the transformation.